Vonoprazan–minocycline dual therapy as a first-line treatment of infection compared with empirical bismuth-containing quadruple therapy - Meng Li; Xiaolei Wang; Xinhong Dong; Guigen Teng; Yun Dai; Weihong Wang (Therapeutic Advances in Gastroenterology)
Background: Increasing antibiotic resistance compromises therapeutic options for Helicobacter pylori ( H. pylori ) infection, especially in penicillin-allergic individuals. Objectives: This trial aimed to assess the efficacy and safety of 14-day vonoprazan–minocycline (VM) dual therapy against bismuth-containing quadruple therapy (B-quadruple therapy), as initial treatment for H. pylori infection. Design: This study was a single-center, open-label, and non-inferiority randomized controlled trial. Methods: In this study, 240 individuals with H. pylori infection who have not received therapy were randomly assigned 1:1 to either the VM dual therapy group (vonoprazan 20 mg plus minocycline 100 mg, administered twice daily) or the B-quadruple therapy group (rabeprazole 10 mg, amoxicillin 1000 mg, clarithromycin 500 mg, and bismuth potassium citrate 220 mg, all administered twice daily). The primary outcome was to evaluate the non-inferiority of eradication rates between the two groups. Secondary outcomes included assessments of AEs and compliance. Results: The eradication rates of VM dual group and B-quadruple therapy group were 87.5% and 88.3%, respectively, by intention-to-treat (ITT) analysis; 92.1% and 94.6% by modified ITT (mITT) analysis; and 92.0% and 95.5% by per-protocol (PP) analysis. The eradication rates of the VM group were non-inferior to those of the B-quadruple therapy group in ITT, mITT, and PP analyses (one-sided p -values were 0.02, 0.01, and 0.02). The incidence of AEs was higher in the B-quadruple therapy group (28.3%) than in the VM group (16.7%, p  = 0.03). Good compliance was achieved in both groups ( p  = 0.60). Conclusion: The VM dual therapy was not inferior to the B-quadruple therapy in the initial treatment of H. pylori infection, and the incidence of AEs was lower compared to B-quadruple therapy. Trial registration: This trial was registered on the Chinese Clinical Trial Registry with the registration number ChiCTR2400081461.